Pola Konsumsi Ultra Processed Food dan Aktivitas Fisik dengan Status Gizi Lebih pada Remaja SMK Kesehatan YHB Sukabumi: Relationship Between Ultra-Processed Food Consumption Patterns and Physical Activity with Overnutrition in Adolescents of SMK Kesehatan YHB Sukabumi - Septiani, Melyana; Sugiatmi, Sugiatmi (Jurnal Ilmu Gizi dan Dietetik, 2026)
The increase in ultra processed food consumption and sedentary lifestyles have become global health issues contributing to the increasing prevalence of overnutrition, especially among adolescents. Adolescents are a vulnerable group because this period involves the formation of long-term lifestyle patterns that can continue into adulthood. This study aims to analyze the relationship between ultra-processed food (UPF) consumption patterns and physical activity with the incidence of overnutrition status in adolescents at SMK Kesehatan Yayasan Harapan Bunda Sukabumi. This study is an analytical observational study with a cross-sectional approach. A total of 115 students were selected as respondents using a simple random sampling technique. Inclusion criteria in this study included active class X students who were willing to participate and signed an informed consent. In addition, to maintain data objectivity, it was ensured that subjects were not undergoing a special diet or certain medications that could affect weight or blood pressure variables. UPF consumption pattern data were collected using the Food Frequency Questionnaire (FFQ), physical activity data with the Physical Activity Questionnaire for Adolescents (PAQ-A), and nutritional status data were measured through BMI/U. Data analysis used the Chi-Square test. The results showed a prevalence of overnutrition of 33.0%. A total of 30.4% of students frequently consumed UPF, and the majority (77.4%) had light physical activity levels. There was a significant relationship between UPF consumption and overnutrition status (p=0.036). In addition, there was also a significant relationship between physical activity and overnutrition status (p=0.021). High UPF consumption and low physical activity are important risk factors for the occurrence of overnutrition in students at SMK Kesehatan Yayasan Harapan Bunda Sukabumi.